SELEKSI DAN KARAKTERISASI MIKROBA LIGNOSELULOLITIK YANG DIISOLASI DARI LIMBAH SERBUK GERGAJI SEBAGAI MEDIA TANAM JAMUR TIRAM (Pleurotus ostreatus) - R Haryo Bimo Setiarto; Iwan Saskiawan (Research Center for Biology-Indonesian Institute of Sciences, 2013)
Spent Mushroom Substrate (SMS) is a composted growing medium that results from the mushroom growing process. The utilization of SMS for biofertilizer or soil conditioner would be an important point in green agriculture. The study revealed the lignocellulolytic activity from 20 isolates of Fungi and 13 isolates of Bacteria which were isolated from sawdust as a spent mushroom substrate of Pleurotus ostreatus. The selected microorganism then would be used as inocullant for the production of biofertilizer using SMS as a main material. The lignocellulolytic system consist of laccase, cellulase and xylanase activity was analyzed. The results shown that among 20 isolates of Fungi, the highest activity of laccase, cellulase, and xylanase was obtained from the isolates 2F1, 2F4 and 2F5. There was (6.153 U, 4.662 U, 3.791U) for laccase, (6.740, 3.711 U, 3.605 U) for cellulase and (6.870 U, 4.673 U, 3.773 U) for xylanase respectively for 2F1, 2F4 and 2F5. Furhtermore, the characterization of the highest lignocellulytic fungi was also conducted. The isolate 2F1 opimally grow in pH 5 at 40oC, isolate 2F4 in pH 9 at 30oC and isolate 2F5 in pH 5 at 30oC. The identification of isolated fungi are in the progress.